Development of an Obstacle Avoiding Robot - Nasucha, Mohammad (Jurnal Sistem Komputer, 2015)
Development of an obstacle avoiding robot model is required as a fundamental step towards a bigger goal, for example development of an autonomous vehicle. An obstacle avoiding robot uses a proximity sensor module, besides other parts. In this case, this robot uses a proximity sensor developed by ourselves. The robot is controlled by a program that is embedded into a microcontroller. The logics produced by the microcontroller are further processed by an interface module, in this case, also developed by ourselves. The interface module translates microcontroller’s logics into voltage and current that can practically drive the two motors. This article provides a report on the project activity, consisting of summary of the design, summary of the development process and report on the running test of the robot. Following the test and program fine-tuning, it has been proven that the robot model operated well just as programmed.